Os desafios da implantação de um serviço regional na baixada santista: estudo de caso sobre o CER - Pinheiro, Michele Darque (2016)
This study's main objective is to understand the challenges of structuring of the health care regionalized networks in Santos: Rede de Cuidados da Pessoa com Deficiência (RCPD) [care network for people with disabilities], from the example of the Centro Especializado de Reabilitação (CER) [rehabilitation specialized center], facility originally designed as a component of federal influence into the conformation of networks for regionalized health care policies. According to literature, one of the greatest obstacles to achieving these regional policies in the country refers to the structure of municipal SUS [health unic system] base. Semi-structured interviews with key informants from the municipal administrations were carried out: directing municipal group; Comissão Intergestores Regional (CIR) [regional managers committee]; and Departamento Regional de Saúde (DRS) [regional health department]. The analysis revealed structural and planning problems, and low technical capacity. Among the most basic challenges, highlights the prevalence of municipalist management culture in the region.